2020
DOI: 10.17159/2309-8988/2020/v36a3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Pressure Recovery for an Induced Draught Fan Arrangement

Abstract: This study investigates the potential gain in operating volume flow rate and static efficiency for an induced draught fan arrangement by reducing the outlet kinetic energy loss. The reduction is achieved through pressure recovery, which is the conversion of dynamic pressure into static pressure. Downstream diffusers, stator blade rows, or a combination of these can recover pressure. Six different discharge configurations are tested for a fan. An annular diffuser with equiangular walls at an angle of 22° from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The effects of turbulence on the mean flow were modelled using the k-ω model of Wilcox [23]. Bekker et al [14] found that this model predicted swirling flow in a conical diffuser with reasonable accuracy.…”
Section: Numerical Solution Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of turbulence on the mean flow were modelled using the k-ω model of Wilcox [23]. Bekker et al [14] found that this model predicted swirling flow in a conical diffuser with reasonable accuracy.…”
Section: Numerical Solution Methodsmentioning
confidence: 99%
“…Bekker et al [14] aimed to find a discharge configuration for the M-fan that produces high pressure recovery coefficients over a range of operating volume flow rates. They considered stator blade rows, conical and annular diffusers, as well as stator-diffuser combinations.…”
Section: D Downstream Diffuser Simulationsmentioning
confidence: 99%
See 3 more Smart Citations